Intention towards car sharing among Generation Y in Malaysia - Chan, Weng Hong; Tan, Eugene; Au, Wing Sze; Yeu, Kai Yik; Tan, Yu Meng (2020)
Automotive industry is about to shift in the present day and it is rapidly advancing due to the trends of various factors such as development of new technology which advocates cost reduction. Car sharing provides users a service to rent vehicles for a short period of time where users make payment pursuant to the time and distance travelled through smartphone application. Presently, there are 5 car sharing organizations including Moovby, Kwikcar, Kayak and Skyscanner, Gocar and Socar operating in Malaysia. Thus, this research was carried out to investigate the associations of influencing elements with the behavioural intention towards Car sharing among Generation Y in Malaysia. Throughout the study, a conceptual framework comprising 5 independent variables was proposed in this research to examine several hypotheses and the impact of variables towards the intention of using Car sharing. In order to gain valid and reliable data, pilot test was carried out and quantitative research was adopted to distribute 300 sets of survey form at the specific sampling location. Furthermore, several methodologies were used to analyze the result of the study. Results of the research discovered that Perceived Usefulness, Social Media Influence, and Affordability are strong catalysts which influence the behavioural intention towards the adoption of Car Sharing while Perceived Ease of Use and Perceived Risk are proved statistically not important on the behavior intention. From an invulnerability perspective, this study stresses the need to take into account the impact of these insights of Car sharing and other relevant organizations theoretically and practically so that an intact service can be developed and provided for users.